Unsteady MHD mixed convection flow of a micropolar fluid over a vertical wedge - Roy, Nepal; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
An analysis is presented to investigate the unsteady magnetohydrodynamic (MHD) mixed convection boundary-layer flow of a micropolar fluid over a vertical wedge in the presence of thermal radiation and heat generation or absorption. The free-stream velocity and surface temperature are assumed to be oscillating in magnitude but not in the direction of the oncoming flow velocity.
Keywords: micropolar fluid; unsteady flow; radiation; heat generation